2022
DOI: 10.1027/2157-3891/a000051
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Perceived Awareness of the South Asian Indian Community During the COVID-19 Pandemic

Abstract: Abstract. The scope of the United Nations Development Programme (2019) emphasizes combating adaptive challenges, building resilience, and sustainability. This systematic review offers a range of perspectives through an in-depth overview of existing literature on the coronavirus disease 2019 (COVID-19) pandemic and the psychological impact it is having on the South Asian community in India. The selected studies focused on COVID-19 were mixed; however, the consensus among articles had themes relating to fear, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Sagar S. Lad, Saajan Bhakta, and Veena Hira present a systematic review in the next article of the existing literature on the psychological impact that the COVID-19 pandemic has had on the South Asian community in India (Lad et al, 2022). Themes that emerged from this review suggested that individuals in this community experienced fear, stress, and anxiety.…”
mentioning
confidence: 98%
“…Sagar S. Lad, Saajan Bhakta, and Veena Hira present a systematic review in the next article of the existing literature on the psychological impact that the COVID-19 pandemic has had on the South Asian community in India (Lad et al, 2022). Themes that emerged from this review suggested that individuals in this community experienced fear, stress, and anxiety.…”
mentioning
confidence: 98%